Transformation of the Decisional Leadership Role - Márta, Erik (International Journal of Engineering and Management Sciences, 2023)
Leadership decision-making is important for the successful functioning of organizations, so it is necessary for leaders to understand the factors that impact their decisions. Decision-making is always the responsibility of the leader, but in a changing world, it becomes an even more crucial factor for success. Making good decisions requires time, experience, and thorough problem-solving skills. In my research, through the analysis of scholarly sources, I have identified several role factors that clearly influence the decision-making process and its implementation. Furthermore, I have developed a self-designed questionnaire to examine the decision-making role in modern organizations. I analyzed the data from 230 respondents using various statistical methods. Based on my findings, conflict management, risk-taking, and a thorough understanding of the problem strongly determine leadership decision-making processes. The ability of leaders to effectively manage conflicts significantly impacts their decisions. Risk-taking is also of key importance, as leaders need to recognize the risks associated with a given situation and make decisions accordingly.